2010
DOI: 10.4319/lo.2010.55.4.1467
|View full text |Cite
|
Sign up to set email alerts
|

Illuminated darkness: Molecular signatures of Congo River dissolved organic matter and its photochemical alteration as revealed by ultrahigh precision mass spectrometry

Abstract: Congo River water was filtered and then irradiated for 57 d in a solar simulator, resulting in extensive photodegradation of dissolved organic matter (DOM). Whole‐water (i.e., unfractionated) DOM was analyzed pre‐ and post‐irradiation using ultrahigh resolution Fourier transform ion cyclotron mass spectrometry (FT‐ICR MS), revealing the following three pools of DOM classified based upon their photoreactivity: (1) photo‐resistant, (2) photo‐labile, and (3) photo‐produced. Photo‐resistant DOM was heterogeneous, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

64
700
2
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 588 publications
(769 citation statements)
references
References 46 publications
64
700
2
3
Order By: Relevance
“…This finding is further ARTICLE substantiated by an independent photodegradation experiment on DOM in a tropical river system 13 . Direct comparison of compounds in our study with those from this independent photodegradation experiment 13 revealed that a striking 78% of compounds associated with lower levels of precipitation and 55% of compounds associated with longer WRT in our study were identified as photoresistant 13 ( Fig. 4b,d).…”
Section: Molecular Associations With Precipitation and Residence Timesupporting
confidence: 66%
See 3 more Smart Citations
“…This finding is further ARTICLE substantiated by an independent photodegradation experiment on DOM in a tropical river system 13 . Direct comparison of compounds in our study with those from this independent photodegradation experiment 13 revealed that a striking 78% of compounds associated with lower levels of precipitation and 55% of compounds associated with longer WRT in our study were identified as photoresistant 13 ( Fig. 4b,d).…”
Section: Molecular Associations With Precipitation and Residence Timesupporting
confidence: 66%
“…4b,d). In addition, 64% of compounds associated with high precipitation and 77% of compounds associated with shorter WRT in our study were independently identified as photolabile 13 (Fig. 4a,c).…”
Section: Molecular Associations With Precipitation and Residence Timesupporting
confidence: 52%
See 2 more Smart Citations
“…In accordance to their findings, we hypothesize that the DOM compounds and the total BC that reach the North Sea undergo mixing and transformation processes from the coast toward the Atlantic on similar timescales of several months and thus retain the intermediate history of the water masses, the 'riverine legacy'. Although taking place on similar timescales, processes influencing DOM and total BC composition are probably different: for example, the BC may respond to changes in temperature or nutrient supply (Fuhrman et al, 2008), whereas the DOM may be more affected by abiotic adsorption/desorption to surfaces (Gogou and Repeta, 2010), flocculation (Mikes et al, 2004) or photochemical processes (Stubbins et al, 2010).…”
Section: Identifying the Key Factors-bcmentioning
confidence: 99%